Agressão : do Homo sapiens ao Homo economicus : desdobramentos políticos e educacionais - Pinto, Viviane Carla de Melo Ribeiro (2017)
This theoretical-analytical research proposes to analyze the phenomenon of aggressiveness and its relation with the process of production of barbarism. The analysis comes from the contribution of the Critical Theory of Society, especially of the philosophy of Theodor Adorno. It tries to find the place for Ethology and Sociobiology, both in the Biological Science fields – education and culture occupy the theoretical speech on this phenomenon produced by their respective representatives, Lorenz (1974) and Wilson (1981). The hypothesis considers that there is a tendency within biological studies to understand and explain the phenomenon of the production of barbarism, linked to scientifically reductionist determinations. What instigated us in the realization of this research was the understanding of how the real arguments to Ethology and Sociobiology support the explanation about the phenomenon related to human destructiveness, which, strictly speaking, have determinations linked not only to the biological facet of the human, but also, and mainly, to the ideologies that underpin actions in the field of science, politics, economics, culture, and society as a whole. In general, the research corroborates the hypothesis. The theories of the authors analyzed here suggest that barbarism, that is, irrational violence associated with ideologies, has a biological origin. Following the ideology of social darwinism, the authors argue that barbarism is the result of the aggressiveness associated to the instinct of animal survival still present in the human being, independently of the social reasons related to them. Therefore, the authors suggest that the materialistic scientific method is the way to understand and intervene in this phenomenon. We conclude that the authors' theories are based on scientism, the fruit of technical-instrumental rationality, typical of the ideology of an economic political system that tends to place on individuals the blame for the social consequences of a society governed by the class domain. Considering that barbarism, despite being a social phenomenon, the result of rational planning, is also associated with the domain of human nature and the manipulation of unconscious and irrational mechanisms, we conclude that even if education alone cannot solve the objective causes Related to barbarism, It‘s believed in a political education that seeks to work the subjective mechanisms linked to the process of the production of barbarism.